2019
DOI: 10.1016/j.advwatres.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The spatio-temporal variability of groundwater storage in the Amazon River Basin

Abstract: In large Tropical River basins such as the Amazon, groundwater plays a major role in the water and ecological cycles with large influences on the rainforest ecosystems and climate variability. However, due to the lack of monitoring networks, Amazon groundwater storage and its variability remain poorly known. Here, we provide an unprecedented direct estimate of the spatio-temporal variations of the anomaly of groundwater storage over the period January 2003 -September 2010 in the Amazon Basin by decomposing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 68 publications
1
57
0
2
Order By: Relevance
“…Uncertainties of this study. The decomposition technique employed in the present study to estimate groundwater is commonly used (see the review from Frappart & Ramillien 64 on GRACE and groundwater for instance), and several specific regional studies proved that it is a powerful tool [68][69][70] . Following Frappart et al 69 , the uncertainty on groundwater storage variations can be computed as follows: Based on Ramillien et al 71 , we assumed that σ TWS < 0.015 m over semi-arid area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties of this study. The decomposition technique employed in the present study to estimate groundwater is commonly used (see the review from Frappart & Ramillien 64 on GRACE and groundwater for instance), and several specific regional studies proved that it is a powerful tool [68][69][70] . Following Frappart et al 69 , the uncertainty on groundwater storage variations can be computed as follows: Based on Ramillien et al 71 , we assumed that σ TWS < 0.015 m over semi-arid area.…”
Section: Methodsmentioning
confidence: 99%
“…The decomposition technique employed in the present study to estimate groundwater is commonly used (see the review from Frappart & Ramillien 64 on GRACE and groundwater for instance), and several specific regional studies proved that it is a powerful tool [68][69][70] . Following Frappart et al 69 , the uncertainty on groundwater storage variations can be computed as follows: Based on Ramillien et al 71 , we assumed that σ TWS < 0.015 m over semi-arid area. Based on Frappart et al 68 and Papa et al 70 , we assumed that: σ SWS < max(△h)σ Sf lood + max(S f lood )σ h Over Chad Lake, the maximum change of water level from one month to another (max(△h)) is 0.15 m, the maximum surface of the lake during the observation period (max(△Sf lood)) is 16,800 km 2 , the associated maximum error (σ Sf lood ) is 8.5 of this latter value, the maximum error on the water level is assumed to 0.03 m (see Birkett, 2000 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of relationships, Guyot et al [14] found that water discharge and solid fluxes were related, but relationships between rainfall and discharge with sediment load have not been further assessed in this Andean sub-basin. Recent studies [15,16] have determined that groundwater is a significant contributor to the water discharge in many Amazon headwater sub-basins and could influence sediment concentrations as well.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the SWE and SM can be simulated from hydrological models such as GLDAS, W3RA and WGHM, of which the GLDAS is the most commonly model. In recent years, there have been many studies of the retrieval of groundwater changes in different regions using the GRACE satellite gravity data and hydrological models, e.g., Mississippi River basin, the North China Plain, Amazon Basin [5][6][7].…”
Section: Introductionmentioning
confidence: 99%